Development and effectiveness of an application-based physical fitness model for Indonesian Police personnel - Suryawana, Awan; Sobarna, Akhmad; Ishak, Muchamad; Hambali, Sumbara (Universitas Tanjungpura, 2025)
Background. Physical fitness is an important component of daily activities. This is especially true for police personnel, but many staff members at the Indonesian Police Staff and Command College find it difficult to maintain due to time constraints and sedentary work. Objectives. This study aimed to develop and assess an application-based fitness training model tailored to their needs, using biomotor components and the FITT principle. Methods. A research and development method based on the ADDIE framework was employed. Tests that evaluate endurance, strength, flexibility, and coordination are given before and after the 12-session intervention involving 70 people. All fitness metrics, such as the amount of land covered in running 12 minutes, the number of push-ups and sit-ups, and agility measured by running running, shows important benefits in the results. A statistical analysis verified the intervention's efficacy. Results. The model was validated by experts and received positive user feedback, particularly for its accessibility and practicality. In addition, based on the results of the effectiveness test using paired sample t-test analysis, it is proven that with the model developed can significantly increase the physical fitness of Sespim staff personnel. Conclusion. This study demonstrates that a structured, time-efficient, and scientifically grounded mobile application can enhance physical fitness in law enforcement contexts. It contributes to digital health innovation and offers a scalable solution for improving occupational fitness in other high-demand sectors.